(3ZjK GdCOH GdPj CfSLe aj TQM dGejI GdYLes - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s ((3eMeO CHhGdSYhO GdTHQGhj s)
(3ChdgG (B:s
(3hHYO, aEf GdbUjOI GdehSheI HdGejI GdYLe, QMe Gddg fGXe pYbOgG s
(3BNQgG (B:s
(3hda aj GdHQOI CYWGag MJi jWjH GdfTQ ef dag ced ZjK GdCOH GdPj CfSLe aj TQM dGejI GdYLe s
(3HChdgG JedcGf CbOegG YGe (B910(3g`s
(3hjNJda GdYfhGf GNJdGakG jSjQkG Hjf fSNI hCNQis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs